Challenges in the assessment and management of pain in non-verbal autistic children: a case report of an osteochondroma revealed by self-aggressive behavior - Laaraje, Azzeddine; Abdelilah, Radi; Abdelhakim, Ourrai; Amal, Hassani; Rachid, Abilkassem (Medical Faculty of Brawijaya University, Indonesia, 2024)
Introduction: To highlight the challenges of identifying and managing pain in non-verbal autistic children through a case of osteochondroma revealed by self-aggressive behavior and to propose a structured diagnostic approach for these complex situations. Case description: We report the case of a 14-year-old girl with severe non-verbal autism spectrum disorder who developed a progressive increase in self-aggressive behavior over 20 months. The evaluation required an in-depth functional behavioral analysis and an adapted clinical examination, complemented by a radiological work-up. Behavioral analysis revealed that the function of the behavioral problems pointed towards an organic origin: an increase in behavior when moving around, a protective limping when dodging with an exacerbation in the evening. The assessment identified a femoral osteochondroma. The introduction of an alternative communication system with analgesic treatment led to an 80% reduction in self-aggressive behavior. Our observation highlights the difficulties in identifying pain in non-verbal ASD patients and the importance of a structured diagnostic approach. The development of alternative communication appears to be a key element in the assessment and management of pain. Conclusion: Pain management in non-verbal ASD patients requires particular vigilance and a systematic diagnostic approach. Early implementation of alternative communication tools is essential to optimize their assessment and treatment.